Determination of heliostat normal using MATLAB / Noraini Idris - Noraini, Idris (2013)
The second explosion in doing research in solar power was in 1997 as consequence to Kyoto Protocol. This protocol outlined the effect of greenhouse emission which endangers the earth. As the result, research in solar power field started to take its path again. This work is a part of solar project to build the first concentrating solar tower (CST) model in South East Asia and was aimed to develop a template using MATLAB programming for the calculation of the heliostat position with respect to the heat absorber mounted at the top of the CST. This template serves as the calculation platform to control the movement of the heliostat using a two-axis motion system so that the sun light is redirected perfectly to the absorber all day long. Since the heliostat normal vector depends on sun position vector, both vectors were calculated by the program and were set as the output of the program. The input from the user will be the Cartesian coordinate of the heliostat and absorber by taking the absorber tower frontal surface and its base as the origin and also the date. The result will be in vector form and will change automatically according to the sun movement. These values will be programmed in the micro controller which will control the motion system of the heliostat, which will be done by a control team. The program´s functionality was proved via several analytical, numerical and three-dimensional graphical verifications and its accuracy which is 0.0005 metre is stated and verified via comparison with four analytical calculations and a graphical verification using SolidWorks. From the verifications, it can be seen that difference of the numerical and analytical results varied from 0.0000 to 0.0005 m which validates the statement of minimum accuracy of the numerical calculated results is 5/10,000 m.